76.1k views
2 votes
7x-7+6(x+1)=6x+3 please help I forget how to solve

User Nsmyself
by
6.1k points

2 Answers

6 votes
First you distribute.
7x - 7 + 6(x + 1) = 6x + 3
7x - 7 + 6x + 6 = 6x + 3
Combine like terms.
13x - 1 = 6x + 3
Add 1 and subtract 6x from both sides.
7x = 4
Divide.
x = 4/7
You can't simplify so that is your answer. I hope this helps love! :)

User Romainl
by
6.1k points
2 votes
7x-7+6(x+1)=6x+3 please help I forget how to solve
7x-7+6(x+1)=6x+3 please help I forget how to solve-example-1
User Jujule
by
5.8k points